Noninvasive prenatal paternity testing by maternal plasma DNA sequencing in twin pregnancies. Issue 12 (14th May 2020) - Xie, Yifan; Qu, Ning; Lin, Shaobin; Jiang, Haojun; Zhang, Yanyan; Zhang, Xiuqing; Liang, Hao; Chen, Fang; Ou, Xueling
Abstract: SNPs, combined with massively parallel sequencing technology, have proven applicability in noninvasive prenatal paternity testing (NIPPT) for singleton pregnancies in our previous research, using circulating cell‐free DNA in maternal plasma. However, the feasibility of NIPPT in twin pregnancies has remained uncertain. As a pilot study, we developed a practical method to noninvasively determine the paternity of twin pregnancies by maternal plasma DNA sequencing based on a massively parallel sequencing platform. Blood samples were collected from 15 pregnant women (twin pregnancies at 9–18 weeks of gestation). Parental DNA and maternal plasma cell‐free DNA were analyzed with custom‐designed probes covering 5226 polymorphic SNP loci. A mathematical model for data interpretation was established, including the zygosity determination and paternity index calculations. Each plasma sample was independently tested against the alleged father and 90 unrelated males. As a result, the zygosity in each twin case was correctly determined, prior to paternity analysis. Further, the correct biological father was successfully identified, and the paternity of all 90 unrelated males was excluded in each case. Our study demonstrates that NIPPT can be performed for twin pregnancies. This finding may contribute to development in NIPPT and diagnosis of certain genetic diseases.